Fatigue Analysis of Pedestal-mounted Crane on Offshore Fixed Platform Using Finite Element Method - Deanna Annisa Dewi; Julendra Bambang Ariatedja (JMES The International Journal of Mechanical Engineering and Sciences, 2019)
The crane is one of the production support facilities on the offshore platform. During operation, it receives a large load, both from the environment and the crane’s operational load, so the crane’s strength and operational safety need to be maintained. Cyclic loading can cause the crane structure to experience fatigue. This evidence shows the importance of analyzing the crane pedestal. How much the load affects the fatigue life of the structure. A previous study on the crane loading effect on the Floating Production Storage and Offloading (FPSO) was provided as a comparison. Local fatigue analysis was performed on the pedestal crane using the Finite Element Method (MEH) and ANSYS Workbench 19.1 software. The validation stage was carried out by comparing the value of the reaction force, moment, and maximum equivalent stress (Von-Mises) on the crane pedestal between the simulation results and hand-calculation. Furthermore, a static simulation was carried out to obtain the stress value as the basis for cyclic loading. A dynamic simulation was carried out based on the stress obtained from the static simulation to determine the structure’s critical point and fatigue life. The fatigue analysis was carried out based on the Palmgren-Miner Theory. It is found that the load that has the most significant influence on crane pedestal fatigue is the operational load with a contribution of 80.7%, wind load of 19.3%, and wave load of 0%. The minimum estimated fatigue life of the crane pedestal structure is 96.5 years or close to 5 times the design life. Compared to the crane in the FPSO in previous studies, the most significant difference lies in the contribution of wave loads, where the wave load on the FPSO has the most considerable contribution to crane structure fatigue (97.8%).